Caspase-2 Substrates: To Apoptosis, Cell Cycle Control, and Beyond - Brown-Suedel, Alexandra N.; Bouchier-Hayes, Lisa (Frontiers in Cell and Developmental Biology, 2020)
Caspase-2 belongs to the caspase family of proteins responsible for essential cellular functions including apoptosis and inflammation. Uniquely, caspase-2 has been identified as a tumor suppressor, but how it regulates this function is still unknown. For many years, caspase-2 has been considered an “orphan” caspase because although it is able to induce apoptosis, there is an abundance of conflicting evidence that questions its necessity for apoptosis. Recent evidence supports that caspase-2 has non-apoptotic functions in the cell cycle and protection from genomic instability. It is unclear how caspase-2 regulates these opposing functions, which has made the mechanism of tumor suppression by caspase-2 difficult to determine. As a protease, caspase-2 likely exerts its functions by proteolytic cleavage of cellular substrates. This review highlights the known substrates of caspase-2 with a special focus on their functional relevance to caspase-2’s role as a tumor suppressor.